ANALISIS PELAKSANAAN MANAJEMEN PEMBELAJARAN MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP 4 KUDUS TAHUN PELAJARAN 2015/2016 (QUALITY, 2017)
This study aimed to describe the implementation of Islamic education learning management; problematics of Islamic education and learning solutions; the output from the learning management implementation of Islamic Education in SMP 4 Kudus. This research subject is the principal, deputy head of affairs curriculum, school committee, teachers and learners. Data collection techniques using the method of observation, interviews, documentation and triangulation. The results showed that: (1) the implementation of Islamic education learning management done well enough that include planning, implementation and evaluation/assessment. (2) Some of the problems that occur in the learning of Islamic education can be overcome quite well with the solutions that have been diajalankan; (3) Output implementation of Islamic education learning management looks pretty good views of the learning achievement of Islamic Religious Education, satisfactory.